The Role of Executive Functions in Object- and Action-Naming among Older Adults. Issue 4 (8th August 2019) - Higby, Eve; Cahana-Amitay, Dalia; Vogel-Eyny, Amy; Spiro, Avron; Albert, Martin L.; Obler, Loraine K.
ABSTRACT: Background/Study Context : Lexical retrieval abilities and executive function skills decline with age. The extent to which these processes might be interdependent remains unknown. The aim of the current study was to examine whether individual differences in three executive functions (shifting, fluency, and inhibition) predicted naming performance in older adults. Methods : The sample included 264 adults aged 55–84. Six measures of executive functions were combined to make three executive function composites scores. Lexical retrieval performance was measured by accuracy and response time on two tasks: object naming and action naming. We conducted a series of multiple regressions to test whether executive function performance predicts naming abilities in older adults. Results : We found that different executive functions predicted naming speed and accuracy. Shifting predicted naming accuracy for both object and action naming while fluency predicted response times on both tests as well as object naming accuracy, after controlling for education, gender, age, working memory span, and speed of processing in all regressions. Interestingly, inhibition did not contribute to naming accuracy or response times on either task. Conclusion : The findings support the notion that preservation of some executive functions contributes to successful naming in older adults and that different executive functions are associated with naming speed and accuracy.